Evaluation of Safety and Efficacy of a Single Lorecivivint Injection in Patients with Knee Osteoarthritis: A Multicenter, Observational Extension Trial - Christopher J. Swearingen; Jeyanesh R. S. Tambiah; Ismail Simsek; Heli Ghandehari; Sarah Kennedy; Yusuf Yazici (Rheumatology and Therapy)
Abstract Introduction Lorecivivint (LOR), a CDC-like kinase/dual-specificity tyrosine kinase (CLK/DYRK) inhibitor thought to modulate inflammatory and Wnt pathways, is being developed as a potential intra-articular knee osteoarthritis (OA) treatment. The objective of this trial was to evaluate long-term safety of LOR within an observational extension of two phase 2 trials. Methods This 60-month, observational extension study (NCT02951026) of a 12-month phase 2a trial (NCT02536833) and 6-month phase 2b trial (NCT03122860) was administratively closed after 36 months as data inferences became limited. Participants received a single intra-articular LOR or placebo (PBO) injection at their parent-trial baseline. The primary outcome was the comparative incidence of serious adverse events (SAEs), with AEs and similar safety measures comprising secondary outcomes. A post hoc baseline-adjusted analysis of covariance (ANCOVA) compared changes from baseline in Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC) Pain and Function subscores and medial joint space width (JSW) between LOR 0.07 mg and PBO groups in a subpopulation of participants with unilateral knee pain and widespread pain low enough to allow participants to differentiate their target knee pain. Results The safety analysis set for the extension study included 495 LOR-treated and 208 control participants, with 409 (82.6%) and 175 (84.1%) remaining at study close, respectively. There were 68 SAEs reported in 38 (5.4%) patients; none were considered treatment-related by investigators. The incidence of AEs was similar between groups. In the post hoc subgroup efficacy analyses, LOR 0.07 mg demonstrated greater mean improvements from baseline compared with PBO in WOMAC pain and function scores out to 12 months post-injection. No between-group differences in medial JSW were observed out to 18 months. Conclusions LOR appeared generally safe and well tolerated. Efficacy analyses on the subset of completer patients demonstrated durable symptom improvements in WOMAC pain and function for at least 12 months compared to PBO after a single injection of LOR. Clinical Trial Registration Number NCT02951026.